2008
DOI: 10.1159/000121604
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade in Medical Patients: A 10-Year Follow-Up Survey

Abstract: Objectives: Cardiac tamponade represents a life-threatening condition that may complicate almost any cause of pericarditis. We conducted a 10-year prospective survey on patients with cardiac tamponade requiring an emergency drainage. Methods: From 1996 to 2005, 114 consecutive patients were admitted to the University Hospital of Brest for medical cardiac tamponade. Data on medical history, and volume, characteristics and histology of the pericardial fluid as well as short- and long-term follow-up data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 23 publications
2
33
1
7
Order By: Relevance
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussioncontrasting
confidence: 98%
“…This finding contrasts with previous clinical studies, which reported malignant diseases as the most common cause of pericardial tamponade, reaching 30-60% of cases [6][7][8][9][10][11]. This shift in tamponade etiology is apparently due to the increase in recent years in the overall number and in the complexity of percutaneous intra-cardiac procedures, as well as the introduction of interventional techniques such as trans-catheter valve replacement and catheter ablation for atrial fibrillation, all reported to be possibly complicated by cardiac tamponade [12][13][14][15].…”
Section: Discussioncontrasting
confidence: 98%
“…Transudative pericardial effusions mainly occur in patients with heart, kidney or liver disease or hypothyroidism and are easy to diagnose. It is important to treat the primary disease, and it is usually not necessary to perform pericardiocentesis [1,2,3,4,5,6]. Exudative pericardial effusions can be divided into malignant and nonmalignant types.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion is a common cardiovascular disease and can be caused by many conditions [1,2,3,4,5,6]. The therapy and prognosis of pericardial effusion mainly depend on the etiology.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study that included all patients with PT showed malignancies as the most common cause with 32% of all cases for PT [9]. A 10-year prospective study of 114 patients with PT demonstrated malignant disease in 74 patients (65%) [10]. In autopsy series, the pericardium was involved in about two-thirds of patients with cancers.…”
Section: Pericardial Disease: Pericardial Constriction and Pericardiamentioning
confidence: 99%
“…Patients with malignant pericardial effusions in lung cancer have an overall worse prognosis than individuals with breast or hematological malignancies. A 10-year survey of patients with PT showed that patients with malignant pericardial effusion carried a high in-hospital mortality with a median survival of 150 days and a 1-year mortality of almost 77% [10]. Considering recurrence is a major issue in malignant pericardial effusion, balloon pericardiotomy or surgical drainage is effective in symptomatic management.…”
Section: Pericardial Disease: Pericardial Constriction and Pericardiamentioning
confidence: 99%